Hoya papaschonii (Apocynaceae: Asclepiadoideae), a new species from southern Thailand with a peculiar corona - Rodda, Michele; Ercole, Enrico (Phytotaxa, 2014)
The new Hoya species, here described and fully illustrated, is an epiphytic shrub with white-cream coloured flowers superficially similar to those of Hoya telosmoides. Its gynostegial corona includes five staminal and five interstaminal lobes, the latter never before observed in Hoya. The placement of the new species within Hoya was confirmed by a phylogenetic analysis based on nuclear ribosomal ITS and 5’-ETS regions, and chloroplast psbA-trnH and trnT-trnL intergenic spacers. It belongs to a group of species including Hoya multiflora and Hoya praetorii, characterised together with H. papaschonii by non-climbing habit, thin leaves lacking basal colleters, and short-lived peduncles.